Multi‐morbidities of allergic rhinitis in adults: European Academy of Allergy and Clinical Immunology Task Force Report. Issue 1 (1st June 2017) - Cingi, C.; Gevaert, P.; Mösges, R.; Rondon, C.; Hox, V.; Rudenko, M.; Muluk, N. B.; Scadding, G.; Manole, F.; Hupin, C.; Fokkens, W. J.; Akdis, C.; et al.
Abstract: This report has been prepared by the European Academy of Allergy and Clinical Immunology Task Force on Allergic Rhinitis (AR) comorbidities. The aim of this multidisciplinary European consensus document is to highlight the role of multimorbidities in the definition, classification, mechanisms, recommendations for diagnosis and treatment of AR, and to define the needs in this neglected area by a literature review. AR is a systemic allergic disease and is generally associated with numerous multi‐morbid disorders, including asthma, eczema, food allergies, eosinophilic oesophagitis (EoE), conjunctivitis, chronic middle ear effusions, rhinosinusitis, adenoid hypertrophy, olfaction disorders, obstructive sleep apnea, disordered sleep and consequent behavioural and educational effects. This report provides up‐to‐date usable information to: (1) improve the knowledge and skills of allergists, so as to ultimately improve the overall quality of patient care; (2) to increase interest in this area; and (3) to present a unique contribution to the field of upper inflammatory disease.